ANALISIS RASIO KEUANGAN DALAM MENILAI KINERJA KEUANGAN PERUSAHAAN PT INDUSTRI JAMU DAN FARMASI SIDOMUNCUL TBK - Ananda, Rizqa; Asnahwati, Asnahwati (JURNAL EKONOMI BISNIS DAN MANAJEMEN (EKO-BISMA), 2025)
This study aims to analyze the financial performance of PT. Industri Jamu dan Farmasi Sidomuncul Tbk for the period 2017–2024 using financial ratio analysis, including profitability, liquidity, and solvency ratios. The analysis was conducted to assess the company’s ability to generate profits, meet short-term obligations, and maintain a sound capital structure amid competition in Indonesia’s herbal and pharmaceutical industry. The research method employed is descriptive quantitative, using secondary data obtained from the company’s annual financial statements. The analysis focused on Net Profit Margin (NPM), Return on Equity (ROE), Return on Investment (ROI), Current Ratio, Quick Ratio, Cash Ratio, Total Debt to Asset Ratio (DAR), and Total Debt to Equity Ratio (DER), which were then compared to industry standards as benchmarks. The results indicate that the average NPM of 26.92% is above the industry standard (20%), reflecting good profitability performance. However, ROE and ROI, at 28.2% and 24.52% respectively, remain below the industry standards (40% and 30%), highlighting the need to improve capital and asset utilization. In terms of liquidity, the Current Ratio of 473.6%, Quick Ratio of 383.8%, and Cash Ratio of 225.62% demonstrate very strong liquidity compared to industry benchmarks. Meanwhile, solvency ratios show a healthy condition, with an average DAR of 13.0% and DER of 15.0%, both far below industry thresholds. Overall, PT. Industri Jamu dan Farmasi Sidomuncul Tbk exhibits strong financial performance in terms of liquidity and solvency, although the effectiveness of capital and asset management in generating profits still requires optimization to achieve a more balanced performance.